Abortion and Human Rights: An Analysis of Indonesian Legal Perspectives in Balancing the Right to Life of the Fetus and Women's Reproductive Health - William Wongkar; I Wayan Gede Artawan Ekaputra (Dinasti Research, 2025)
Abortion in Indonesia is a complex legal and ethical issue, sparking debates concerning human rights (HR) from the perspective of the fetus's right to life and women's reproductive health rights. Legally, abortion is governed by the 1945 Constitution, Pancasila, Law No. 39 of 1999 on Human Rights, Law No. 1 of 2023 on the Criminal Code, and Law No. 17 of 2023 on Health. Human rights related to abortion encompass two primary perspectives: the fetus's right to life as part of humanitarian principles and women's right to reproductive health, including access to abortion under specific conditions such as medical indications or cases of rape. While abortion is generally viewed as violating humanitarian principles, Indonesian law accommodates certain exceptions to save the mother’s life or provide justice for victims of sexual violence. This study aims to foster public awareness that abortion in Indonesia remains strictly regulated within the legal framework, balancing human rights and societal moral values.